Assessing Biobehavioural Self‐Regulation and Coregulation in Early Childhood: The Parent‐Child Challenge Task. Issue 1 (5th April 2016) - Lunkenheimer, Erika; Kemp, Christine J.; Lucas‐Thompson, Rachel G.; Cole, Pamela M.; Albrecht, Erin C.
Abstract : Researchers have argued for more dynamic and contextually relevant measures of regulatory processes in interpersonal interactions. In response, we introduce and examine the effectiveness of a new task, the Parent–Child Challenge Task, designed to assess the self‐regulation and coregulation of affect, goal‐directed behaviour, and physiology in parents and their preschoolers in response to an experimental perturbation. Concurrent and predictive validity was examined via relations with children's externalizing behaviours. Mothers used only their words to guide their 3‐year‐old children to complete increasingly difficult puzzles in order to win a prize ( N = 96). A challenge condition was initiated midway through the task with a newly introduced time limit. The challenge produced decreases in parental teaching and dyadic behavioural variability and increases in child negative affect and dyadic affective variability, measured by dynamic systems‐based methods. Children rated lower on externalizing showed respiratory sinus arrhythmia (RSA) suppression in response to challenge, whereas those rated higher on externalizing showed RSA augmentation. Additionally, select task changes in affect, behaviour, and physiology predicted teacher‐rated externalizing behaviours four months later. Findings indicate that the Parent–Child Challenge Task was effective in producing regulatory changes and suggest its utility in assessing biobehavioural self‐regulation and coregulation in parents and their preschoolers. Copyright © 2016 John Wiley & Sons, Ltd.